Bisretinoid Photodegradation Is Likely Not a Good Thing - Ueda, Keiko (Adv Exp Med Biol, 2018)
Retinaldehyde adducts (bisretinoids) accumulate in retinal pigment epithelial (RPE) cells as lipofuscin. Bisretinoids are implicated in some inherited and age-related forms of macular degeneration that lead to the death of RPE cells and diminished vision. By comparing albino and black-eyed mice and by rearing mice in darkness and in cyclic light, evidence indicates that bisretinoid fluoro-phores undergo photodegradation in the eye (Ueda et al. Proc Natl Acad Sci 113:6904–6909, 2016). Given that the photodegradation products modify and impair cellular and extracellular molecules, these processes likely impart cumulative damage to retina.